2019
DOI: 10.3389/fcimb.2019.00004
|View full text |Cite
|
Sign up to set email alerts
|

Higher Risk of Stroke Is Correlated With Increased Opportunistic Pathogen Load and Reduced Levels of Butyrate-Producing Bacteria in the Gut

Abstract: Objective: Gut microbiota is a newly identified risk factor for stroke, and there are no large prospective studies linking the baseline gut microbiome to long-term risk of stroke. We present here the correlation between the gut microbiota and stroke risk in people with no prior stroke history.Methods: A total of 141 participants aged ≥60 years without prior history of stroke were recruited and divided into low-risk, medium-risk, and high-risk groups based on known risk factors and whether they were suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
118
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 50 publications
10
118
4
1
Order By: Relevance
“…Butyrate is not only a primary energy source for colonocytes, but also can maintain intestinal homeostasis through anti-in ammatory actions via inhibiting nuclear factor kappa β, and histone deacetylation by promoting epithelial barrier function [16,79]. Previously, lower abundance of butyrate-producing bacteria and fecal butyrate were found in stroke patients as higher risk factors [80]. Bacteroidetes from Firmicutes mainly produce acetate and propionate, while Butyrate is mainly produced by phylum Firmicutes i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is not only a primary energy source for colonocytes, but also can maintain intestinal homeostasis through anti-in ammatory actions via inhibiting nuclear factor kappa β, and histone deacetylation by promoting epithelial barrier function [16,79]. Previously, lower abundance of butyrate-producing bacteria and fecal butyrate were found in stroke patients as higher risk factors [80]. Bacteroidetes from Firmicutes mainly produce acetate and propionate, while Butyrate is mainly produced by phylum Firmicutes i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the microbiome may also be a risk factor leading to disease, including stroke and stroke-related comorbidities. A prospective study showed that opportunistic pathogens, including Enterobacteriaceae and Veillonellaceae, and lactateproducing bacteria, including Lactobacillus and Bifidobacterium, were increased in patients who had a high risk of stroke compared to low risk controls [17]. Changes in the microbiome of atrisk or post-stroke patients can also be mimicked in rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…The estrobiome is the collective term for gut bacterial genes whose products metabolize estrogens Blaser, 2011, Kwa et al, 2016) Tamboli et al 2004). A recent large human study showed that baseline dysbiosis was corelated with an increased risk of stroke (Zeng et al, 2019). Similarly, recent preclinical studies have also shown that age-related differences in stroke outcomes are linked to a constitutive difference in microbial communities.…”
Section: Discussionmentioning
confidence: 98%